Efektifitas Penerapan Program Supervisi Klinis terhadap Peningkatan Kualitas Asuhan Keperawatan dan Kinerja Perawat - Lia Huslianti, Ratu (Journal of Comprehensive Science, 2025)
This study aims to examine the effectiveness of implementing a clinical supervision program to improve the quality of nursing care and nurse performance using the systematic literature review (SLR) method. Clinical supervision programs are considered as one intervention that has the potential to improve the quality of health services, especially in the nursing context. In this research, various relevant articles and research related to the application of clinical supervision in various hospital settings and health facilities were analyzed to identify their impact on increasing nurse competency and the quality of care provided to patients. Based on the results of the analysis of 10 articles that met the inclusion criteria, it was found that the implementation of structured clinical supervision can improve nurses' technical skills, interpersonal communication and patient satisfaction, which in turn improves the quality of nursing care. Apart from that, clinical supervision has also been proven to contribute to increasing nurses' motivation and performance in carrying out their professional duties. The results of this research suggest that clinical supervision programs should be integrated more intensively in the professional development of nurses, with an emphasis on practical learning aspects and ongoing emotional support.